PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF STAD DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH DASAR NEGERI 054938 ALUR DUA KECAMATAN SEI LEPAN PANGKALAN BRANDAN KABUPATEN LANGKAT - Uthman Uthman (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The objectives of this research were to discover: (1) the difference in learningachievement of Islam Religion Education of students taught by cooperativeinstructional strategy STAD type and student taught by expository instructionalstrategy, (2) the a difference of learning style Islam Religion education with visual,auditory and kinesthetic, learning style, and (3) the interaction between instructionalstrategy and learning style in affecting learning achievement of learning style Islamreligion education. The population was Grade V students of Primary School IntiNumber SD Negeri 054938 Alur Dua Sei Lepan Pangkalan Brandan Langkat regencyconsisting of three classes. The sample chosen for instructional class using STAD wasclass Vc with 40 students, while those taught by expository was class Vb with 40students. The results of the findings were: (1) the average of Islam Religion Educationof students taught by STAD instructional strategy ( X = 29,95) was higher than theaverage of students taught by expositoyi instructional strategy ( X = 28,62) with Fcount= 12,46 > Ftable = 3, 972), the avarage learning achievement of Islam religion educationwith kinesthetic learning style ( X = 29,77) and visual learning style ( X = 25.35) withFcount = 5,92 > Ftable = 3,972, and (3) there was an interaction between instructionalstrategy and learning style toward students learning achievement Islam Religioneducation with Fcount = 23.84 > Ftable = 3,972.